Next step in the development of mesoprogestins: the preclinical profile of EC313 - Błaszczak-Świątkiewicz, K.; Krupa, A.; Mnich, E.; Elger, W.; Oettel, M.; Nair, H.; Wierzbicki, M.; Sieroszewski, P.; Shaked, Z. (Frontiers in Endocrinology, 2023)
Introduction The pharmacological target for progesterone, different progestins, and Selective Progesterone Receptor Modulators (SPRMs) is the nuclear progesterone receptor (PR). EC313 is a new member of a subgroup of SPRMs, mesoprogestins, which combine especially PR- agonistic and PR-antagonistic activities in one molecule. Methods The suitable in vivo-model for the differentiation of SPRMs from the subgroup of mesoprogestins is the estrogen-primed juvenile rabbit endometrium assay (McPhail Assay). Remarkably, in contrast to other well-known SPRMs with no agonistic effects in this test, EC313 shows clear partial PR-agonistic effects that are higher than that of the well-known mesoprogestin Asoprisnil which already demonstrated remarkable clinical effectiveness for the treatment of uterine fibroids and endometriosis. The findings from the guinea pig studies presented here can be the impetus for further preclinical development of EC313. This model shows the same features for the termination of pregnancy by antiprogestins such as Mifepristone and Ulipristal acetate (UPA) in humans. Moreover, it is possible to distinguish between progestational and anti-progestational activities in the same experiment. Results The EC313 treatment reveals PR dominance in the genital tract and inhibits unopposed estrogenic effects. In very high doses (30.0 mg/animal/day subcutaneously (s.c.)) given twice on pregnancy days 43 and 44, no premature labor was induced (in contrast to UPA, dosed at 10.0 and 30. mg/animal/day s.c.). The anti-ovulatory activity of EC313 exceeds that of Ulipristal acetate or Mifepristone. EC313 binds to the steroid receptors in vitro with a similar affinity as the natural ligand progesterone. At the glucocorticoid receptor (GR) EC313 acts as a weak inhibitor. Minor activities at the human androgen receptor (AR) and mineralocorticoid receptor (MR) are considered negligible. No binding to the estradiol receptor was detected. In contrast to some in vitro-receptor findings, estrogenic, anti-estrogenic, androgenic, anti-androgenic, glucocorticoid, and anti-glucocorticoid actions were absent in vivo. The tissue selectivity of EC313 was demonstrated previously by reducing the growth and proliferation of uterine fibroids in animal models (lowest effective dosage 0.1 mg/kg/day s.c.).. As shown in this article, the anti-fibroid activity of EC313 was confirmed with a 10 times lower dosage (0.01 mg/kg/day s.c.). It was also shown that EC313 reduces the growth of endometriotic lesions in a human xenograft immune-deficient (NOD-SCID) mice model with a comparatively very low dosage range. In the aforementioned EC313 activity model, UPA was tested as the reference compound, the clinical effectiveness of which has already been demonstrated. Discussion For an explanation of these findings, the possibility is discussed that the mixed agonistic/antagonistic feature of EC313 is tissue target-specific based on its super-additive synergism characteristic for active bifunctional agents. In conclusion, the specific pharmacodynamic profile of this compound opens the possibility for the development of a drug with a distinct pharmaco-endocrinological profile against uterine fibroids, endometriosis, and other PR-dependent gynecological diseases.